2016
DOI: 10.4049/jimmunol.1600266
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Is an Essential Mediator of IFN-γ–Dependent Immunity to Mycobacterium tuberculosis

Abstract: The cytokine IFN-γ coordinates macrophage activation and is essential for control of pathogens including Mycobacterium tuberculosis. However, the mechanisms by which IFN-γ controls M. tuberculosis infection are only partially understood. Here, we show that the transcription factor HIF-1α is an essential mediator of IFN-γ dependent control of M. tuberculosis infection both in vitro and in vivo. M. tuberculosis infection of IFN-γ activated macrophages results in a synergistic increase in HIF-1α protein levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
250
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(281 citation statements)
references
References 42 publications
26
250
3
2
Order By: Relevance
“…We find that during M. tuberculosis infection NO is required for IFN-γ dependent stabilization of HIF-1α, a transcription factor we have recently shown to be critical for control of M. tuberculosis infection (16). Interestingly, we find that HIF-1α and iNOS are linked in a positive feedback loop during IFN-γ activation of M. tuberculosis infected macrophages.…”
Section: Introductionmentioning
confidence: 78%
“…We find that during M. tuberculosis infection NO is required for IFN-γ dependent stabilization of HIF-1α, a transcription factor we have recently shown to be critical for control of M. tuberculosis infection (16). Interestingly, we find that HIF-1α and iNOS are linked in a positive feedback loop during IFN-γ activation of M. tuberculosis infected macrophages.…”
Section: Introductionmentioning
confidence: 78%
“…To assess growth, we used a luminescent reporter strain, TB-Lux, that expresses the bacterial luminescent operon lux CDABE that we have shown to be a linear reporter of bacterial number in macrophages. 23 Resting and IFN- γ -activated BMDM were infected with TB-lux and treated with gefitinib or gefitinib and IFN- γ for 4 days post-infection. As expected, gefitinib treatment inhibited replication of M. tuberculosis in macrophages, as did activation of the macrophages with IFN- γ (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study also showed that in a high-dose model of Mtb Erdman infection, mice deficient in HIF1α in myeloid cells demonstrated increased susceptibility to infection (40). HIF1α was shown to induce IFN-γ-mediated killing by activating aerobic glycolysis (40), suggesting that the pathways that modulate host protection versus pathology are finely balanced. However, the above studies were conducted in B6 mice; further studies on the role of HIF1α in human or nonhuman primate Mtb infection models may provide additional insights into the role of HIF1α in inducing pathology, as shown here in necrotic mouse models, versus protection as shown in the non-necrotic B6 mouse model of Mtb infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a systemic Mycobacterium avium model of infection, mice deficient in HIF1α expression in myeloid cells demonstrated increased liver necrosis (39). A recent study also showed that in a high-dose model of Mtb Erdman infection, mice deficient in HIF1α in myeloid cells demonstrated increased susceptibility to infection (40). HIF1α was shown to induce IFN-γ-mediated killing by activating aerobic glycolysis (40), suggesting that the pathways that modulate host protection versus pathology are finely balanced.…”
Section: Discussionmentioning
confidence: 99%